2016
DOI: 10.3791/53457
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Catheterization of the Intestinal Lymph Trunk and Collection of Lymph in Neonatal Pigs

Abstract: Catheterization of the intestinal lymph trunk in neonatal pigs is a technique allowing for the long-term collection of large quantities of intestinal (central) efferent lymph. Importantly, the collection of central lymph from the intestine enables researchers to study both the mechanisms and lipid constitutes associated with lipid metabolism, intestinal inflammation and cancer metastasis, as well as cells involved in immune function and immunosurveillance. A ventral mid-line surgical approach permits excellent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Big animals (pig, dog) are preferred to smaller ones (rat and mouse) because of physiological and anatomical keenness ( e.g. , biliary secretion) to human 266 , 267 . Moreover, it is easy to simulate pre- and post-prandial states in big animals than in small ones which display constant bile flow regardless of dietary 81 .…”
Section: Models For Evaluation Of Lymphatic Transportmentioning
confidence: 99%
“…Big animals (pig, dog) are preferred to smaller ones (rat and mouse) because of physiological and anatomical keenness ( e.g. , biliary secretion) to human 266 , 267 . Moreover, it is easy to simulate pre- and post-prandial states in big animals than in small ones which display constant bile flow regardless of dietary 81 .…”
Section: Models For Evaluation Of Lymphatic Transportmentioning
confidence: 99%
“…At 13 wk of age (7 wk of diet), swine were unfed overnight and weighed and general anesthetic was induced. A cannula was implanted into the superior mesenteric lymph duct and lymph was collected for 1 h into an EDTA-coated Vacutainer as previously described by Uwiera et al (42). Total lymph volume as well as lymph flow rate (lymph volume per hour) was recorded and exsanguination was performed under anesthetic prior to tissue collection.…”
Section: Mesenteric Lymph Duct Cannulation and Nascent Lymph Collectionmentioning
confidence: 99%
“…Additionally, we also found that SREBP2, INSIG1, LDL receptor, and HMGCR were all down-regulated in swine fed the Western diet. A study in hamsters reported that cholesterol feeding causes a decrease in the intestinal gene expression of HMG-CoA reductase, SREBP2, and the LDL receptor, thus leading to reduced cholesterol synthesis (39,42,60). Insig1 reciprocally controls cholesterol synthesis; however, because the ratio of SREBP cleavage-activating protein (SCAP) to Insig cumulatively regulates this process, it is difficult to infer anything just from the expression of Insig1 (61).…”
Section: Diet and Birth Weight Impacting Intestinal Gene Expressionmentioning
confidence: 99%
“…localization of treatments in specific locations in the small intestine). Furthermore, the collection of both intestinal and non-intestinal lymph provides insight to effects of diets, therapeutic agents, and modulators of immune function on immune surveillance and processes involved in the pathogenesis of IBD ; R. R. E. Uwiera, Mangat, Kelly, T. C. Uwiera, & Proctor, 2016). Importantly, the use of larger animal models to study IBD facilitates the collection of large quantities of tissue without pooling samples, and thereby reduces the numbers of animals required.…”
Section: Considerations For Choosing the Most Appropriate Animal Modelmentioning
confidence: 99%